An evaluation system for characterization of polysaccharides from the fruiting body of Hericium erinaceus and identification of its commercial product. (25th June 2015) - Wu, Ding-Tao; Li, Wen-Zhi; Chen, Jun; Zhong, Qian-Xia; Ju, Yao-Jun; Zhao, Jing; Bzhelyansky, Anton; Li, Shao-Ping
Highlights: An evaluation system was proposed to identify polysaccharide from Hericium erinaceus product. The colorimetric assay, HPSEC–MALLS–RID, GC–MS, and PACE were performed. Polysaccharides in H. erinaceus collected from different regions were similar. The commercial product of H. erinaceus was successfully authenticated. Abstract: An evaluation system including colorimetric assay with iodine and potassium iodide, HPSEC–MALLS–RID analysis, GC–MS analysis, and saccharide mapping based on PACE analysis was proposed for the identification and discrimination of commercial product of Hericium erinaceus based on the chemical characters of polysaccharides in H. erinaceus fruiting body collected from different regions of China. The results showed that the molecular weights, the compositional monosaccharides and the glycosidic linkages of polysaccharides in H. erinaceus collected from different regions of China were similar, respectively. However, polysaccharides in the widely consumed product of H. erinaceus in China were significantly different from those of H. erinaceus fruiting body. The implications from these results were found to be beneficial to improve the quality control of polysaccharides from the H. erinaceus fruiting body, and suggest that the proposed evaluation system could be used as a routine approach for the quality control of polysaccharides in other edible and medicinal mushrooms.